(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Emergency surgery is essential for life-threatening conditions requiring immediate intervention. The stress response from surgery prolongs recovery, leading to higher mortality rates, hence the need for ERAS protocols. Objectives: This study aims to evaluate the impact of Enhanced Recovery After Surgery (ERAS) protocols on postoperative outcomes in patients undergoing emergency laparotomy for gunshot injuries at BKMC Swabi Pakistan. Study design: A randomized controlled trial Duration and place of study: Department of Surgery, in collaboration with the Department of Anesthesiology from 05-august 2020 to 05-august 2021. Materials and Methods: A randomized controlled trial at BKMC Swabi involved patients aged 18+ with firearm injuries undergoing emergency laparotomy. Patients were randomly assigned to ERAS or conventional care groups. Outcomes measured included length of stay, morbidity, and 30-day mortality, with secondary outcomes of bowel movement time and postoperative complications. Results: It was observed that the LOS of stay in the ERAS group was 4 (1) days whereas in the concurrent care group, this number was 7 (3) days and a statistically significant difference was noticed (p ≤ 0. 001). Likewise, in the conventional care group postoperative complications such as, a chest infection and surgical site infections moderate concerns.